IN VITRO ASSESSMENT OF TINOSPORA CORDIFOLIA STEM FOR ITS ANTIOXIDANT, FREE RADICAL SCAVENGING AND DNA PROTECTIVE POTENTIALS - NIKHIL BABAN GHATE,; DIPANKAR CHAUDHURI,; NRIPENDRANATH MANDAL, (International Journal of Pharma and Bio Sciences, 2013)
Antioxidants have reactive oxygen species (ROS) scavenging ability with great relevance in the prevention of oxidative stress. The present study aimed to examine the antioxidant and ROS scavenging activities of 70% methanolic extract of Tinospora cordifolia. The plant was found a significant source of carbohydrate, alkaloid, ascorbic acid, tannin, phenolic and flavonoid compound. The extract was found to be an antioxidant with a TEAC value of 0.257 ± 0.03. The extract has shown different radical scavenging activity and 128.86± 4.07 µg/ml, 103.17 ± 5.75 µg/ml, 51.98 ± 4.80 µg/ml, 327.38 ± 21.44 µg/ml, were determined as IC50 value for hydroxyl radical, superoxide, nitric oxide, and hypochlorous acid respectively. The plant inhibits lipid peroxidation with an IC50 of 75.86 ± 2.16 µg/ml. The extract also has good DNA protective potential. In other words, the present results provide evidence that T. cordifolia acts as an antioxidant and DNA protector.